Does Banks Credit to Micro Small and Medium Enterprises (MSME) Reduce Poverty? New Evidence from Nigeria - Ogboi, Charles; Fashakin, Olusesan; Aboyeji, Oyekanmi Moses; Awonusi, Temitope Olarewaju; Adeola, Adedeji Omosunmibo; Onyeri, Ngozi Blessing (Archives of Business Research, 2025)
Poverty remained one of the most pressing socio-economic challenges in Nigeria, despite the country's abundant natural and human resources. Over 40% of Nigerians live below the poverty line, with poverty incidence disproportionately affecting rural areas. However, the effect of bank credits such as Deposit Money Bank’s Loan (DMBL), Microfinance Bank Loans (MFBL), Deposit Finance Institution Loan (DFIL) to Micro, Small, and Medium Enterprises (MSMEs) on poverty incidence remained underexplored in the Nigerian context. This study examined the effect of banks’ credit to MSMEs on poverty incidence in Nigeria. The study adopted quantitative research design. Time series data were obtained from Central Bank of Nigeria spanning 24 years (2000 to 2023). Descriptive and inferential (multiple linear regression) statistics were used to analyzed the data at 5% level of significance. Result showed that banks’ credits to MSME significantly affected MSMEs (Adj. R2= 0.83; F(3,20) = 33.18; P = 0.00). Specifically, DMBL has negative but insignificant effect on poverty (β1= -0.60, p =0.84); MFBL has negative and significant effect on poverty (β2 = - 1.51, p = 0.04); DFIL has negative and significant effect on poverty (β3 = -1.09, p=0.05). The study concluded that banks credit to MSME reduced poverty incidence in Nigeria. The study then recommended that management of the various categories of banks should implement measures to enhance loan accessibility for MSMEs. This includes lowering interest rates, reducing collateral requirements, and streamlining application processes to encourage more small businesses to access credit.